Lifestyle medicine prescriptions for personal and planetary health - Neha Pathak (Elsevier, 2021)
The impact of climate change goes farther than temperature rise and environmental disruptions into the realm personal and community health. Weather disruption, biodiversity loss and the degredation of ecosystems threaten the very foundation of health and wellbeing, with the risk for suffering amplified among those with chronic conditions, a large and growing subset of the global population. Here we focus on how Lifestyle Medicine (LM) interventions can help individuals and communities mitigate and adapt to the health risks of climate change. We will also share how the pillars of LM, as defined by the American College of Lifestyle Medicine (ACLM), can be deployed to deliver these interventions in the healthcare and community settings as a prescription for a greener, healthier world. We will end with how these interventions align with the strategic initiatives of the American College of Lifestyle Medicine.